Falling in love with a [sperm] warrior: conscripting women’s wombs to the dissemination of a religio-political ideology. - Bokek-Cohen, Ya'arit (Journal of Gender Studies, 2017)
This article focuses on the screening and marketing of sperm in Israel as a mechanism for enlisting women’s wombs to political goals. The background for the analysis is the recent rise in demand for sperm from combat soldiers during the war between Israel and Hamas. The data-set for the project is comprised of multiple sources which converge to provide evidence for the transfusion of Zionist ideology into sperm donation. The article suggests the compatibility of the venerated status gained by donors who are Israeli Defense Force combatants with Zionist militarism. The banks screen candidates for sperm donation based on their military service and military health profile. The discursive climate which glorifies ‘warriors’ permeates sperm marketing, contributing to the cultural reproduction of a militaristic ideology. The article concludes by contending that sperm banks provide a platform for a subversive discourse that triggers Enloe’s thesis of patriotic motherhood and the role of women in the process of militarization.